Impact of benznidazole treatment on the functional response of Trypanosoma cruzi antigen-specific CD4+CD8+ T cells in chronic Chagas disease patients. - Elena Pérez-Antón; Adriana Egui; M Carmen Thomas; Concepción J Puerta; John Mario González; Adriana Cuéllar; Manuel Segovia; Manuel Carlos López (Public Library of Science (PLoS), 2018)
Chagas disease is caused by Trypanosoma cruzi. The persistence of the parasite is associated with the disease chronicity and the impairment of the cellular immune response. It has been reported that the CD4+CD8+ T cell population expands in chronic Chagas disease patients. Few studies have focused on this subset of cells, and very little is known about the impact of antiparasitic treatment on this population.Thirty-eight chronic Chagas disease patients (20 asymptomatic and 18 symptomatic) and twelve healthy controls were enrolled in this study. Peripheral blood mononuclear cells were stimulated with soluble T. cruzi antigens to analyze the production of cytokines and cytotoxic molecules by CD4+CD8+ T cells before and after benznidazole treatment. Additionally, expression and co-expression of five inhibitory receptors in these patients after treatment were studied using a multiparameter flow cytometry technique.The frequency of CD4+CD8+ T cells was higher in chronic Chagas disease patients compared with healthy donors. Furthermore, a higher ratio of CD4+CD8low/CD4+CD8high subpopulations was observed in chronic Chagas disease patients than in healthy donors. Additionally, CD4+CD8+ T cells from these patients expressed and co-expressed higher levels of inhibitory receptors in direct proportion to the severity of the pathology. Benznidazole treatment reduced the frequency of CD4+CD8+ T cells and decreased the ratio of CD4+CD8low/CD4+CD8high subpopulations. The co-expression level of the inhibitory receptor was reduced after treatment simultaneously with the enhancement of the multifunctional capacity of CD4+CD8+ T cells. After treatment, an increase in the frequency of T. cruzi antigen-specific CD4+CD8+ T cells expressing IL-2 and TNF-α was also observed.CD4+CD8+ T cells could play an important role in the control of T. cruzi infection since they were able to produce effector molecules for parasite control. Benznidazole treatment partially reversed the exhaustion process caused by T. cruzi infection in these cells with an improvement in the functional response of the T. cruzi antigen-specific CD4+CD8+ T cells.